2012
DOI: 10.1248/yakushi.12-00080
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Group Work as a Teaching Strategy for Long-Term Practical Training in the 6-Year Pharmaceutical Education

Abstract: At the initiation of long-term practical training in the 6-year pharmaceutical education, there are many issues to be solved. For example, it is necessary for teaching pharmacists, who are in charge of both sta‹ng and teaching pharmacy students, to manage their workload with other staŠ pharmacists. To overcome this situation and to improve the motivation of teaching pharmacists towards student practical training, we twice held group work (GW) sessions for teaching pharmacists, and then evaluated whether such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The support of the peer group, as reported by Kubo et al, [14] can greatly assist collaborative learning; this has been demonstrated in this case study where students gained insight into both the subject matter and how their course was preparing them in a relevant manner for their future career.…”
Section: Discussionmentioning
confidence: 59%
“…The support of the peer group, as reported by Kubo et al, [14] can greatly assist collaborative learning; this has been demonstrated in this case study where students gained insight into both the subject matter and how their course was preparing them in a relevant manner for their future career.…”
Section: Discussionmentioning
confidence: 59%